Primary pulmonary osteosarcoma in a dog with associated hypertrophic osteopathy - Seiler, R. J. (SAGE Publications, 1979)
Primary pulmonary sarcomas are uncommon in animals and man [4, 6, 101 and primary osteosarcoma in the lung of man is particularly rare [5, 8, 91. In the dog only five probable cases of primary pulmonary osteosarcoma have been reported [2]; other extraskeletal osteosarcomas occur occasionally [ 1,7]. Primary osteosarcomas of the upper airway also have beenreported [3]. Hypertrophic osteopathy occasionally is found in the dog and is most frequently associated with primary or metastatic lung neoplasia, notably metastatic osteosarcoma [2].